PENINGKATAN KEMAMPUAN KOSA KATA BAHASA INGGRIS ANAK AUTIS MELALUI PERMAINAN KARTU DAN GERAK LAGU - Firdaus, Firdaus; Edyyul, Ilham Akerda; Septia, Wia; Earnestly, Femi (Jurnal Pendidikan Dasar, 2023)
Abstract: This research aimed to improve the English vocabulary of autistic children in comprehension and pronunciation through the use of card games and song movements. The research subjects used total sampling with 16 students. This form of research was a class action with a design in the form of planning, action, observation and reflection. This research consisted of two cycles. Data collection was carried out using tests, interviews and observations. The analytical method used was descriptive quantitative. The research results showed that through learning card games and song movements, students could improve their English vocabulary skills in understanding and pronunciation. In the results of cycle I, post test I was carried out, showing a comprehension score of 2.40 and a pronunciation score of 2.23. This means there was an increase compared to the pre-test with 0.94 marks for understanding and 0.67 for pronunciation. In cycle II, post-test II was carried out with results of 3.61 in understanding and 3.77 in pronunciation. The increase occurred by 1.21 in understanding and 1.54 in pronunciation. These results showed that the combination of learning card games followed by song movement games could improve English vocabulary skills in the understanding and pronunciation of students at the Autism Mitra Ananda Special Need School. The increase in vocabulary pronunciation was greater than understanding. Key words: SLB Autism Mitra Ananda, Vocabulary, Card Games, Song Movement